Analysis Of Customer Satisfaction On The Application Of The Covid-19 Protocol At The Inter-City Bus Terminal - Irfan Rifai, Andri; Fazadi Rafianda, Dimar; Isradi, Muhammad; Mufhidin, Amar (Department of Information Technology, Universitas Malikussaleh, Aceh Utara, Indonesia, 2021)
The rise of the Covid-19 outbreak in Indonesia, especially Bekasi City, it is very strong influencing the existing regulations at the Bekasi city main terminal the author wants to research customer satisfaction with the facilities and implementation of the Covid-19 protocol at terminal bus in Bekasi City. This study aims to describe the perception of satisfaction customers using a questionnaire against health protocols in terminal facilities in the terminal main bus Bekasi. This method is carried out by direct survey to the location research in order to obtain data on existing facilities. Then also with distributed questionnaires to 90 respondent. The population taken in the study these are customers at the Bekasi City Main Terminal. The data processed in this study uses Microsoft Excel and SPSS versions 24 and 16 with method used by Importance Performance Analysis (IPA). It was found that the performance level facilities and customer satisfaction that must be considered in A Quadrant. The main priority is for smoking prohibition, drainage, special access pedestrians / passengers with special needs, luggage storage, charging station, and the facilities for a nursing room.